EFEKTIVITAS METODE SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN - Feby Inggriyani; Annisa Aisyatun (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine the increase in students' reading comprehension using the SQ3R method with the problem of low comprehension in understanding reading texts. The research method is a quasi-experimental non-equivalent control group design. The population is class IV students with a purposive sampling technique. The data collection technique used is a test. The calculation uses the Mann Whitney test. Based on data analysis, the experimental class obtained an N-Gain test result of 0.73 and 0.67 in the control class. Thus, there is an average increase in reading comprehension skills using the SQ3R method compared to conventional learning through lectures.